Effects of fire on scuttle flies (Diptera: Phoridae) in a pine forest in Poland - Durska, Ewa (Entomologica Fennica, 2015)
Ecological consequences of fire on the scuttle fly communities were investigated in a pine forest in Poland (Garwolin Forest). Data from 1,243 identifiable individuals, representing 48 species, were used. The scuttle fly communities in fire-affected plots were similar in terms of the number of species but less diverse than those in an undisturbed reference plot. The response of the flies to the fire was species-specific. Four Megaselia species (M. brevicostalis, M. nigriceps, M. elongata and M. obscuripennis) were most numerous in the plot most affected by fire. Approximately three years after the fire the scuttle fly communities were relatively similar to those found in a clear-cut pine plantation (Bialowieza Primeval Forest) as well as to those in post-windthrow habitats (Pisz Forest) in which logs were removed or left. The Megaselia species are the winners in the fire affected habitats and seem to be more stress-tolerant than other genera ofthe scuttle flies.